Study on the dynamic response characteristics of hydraulic support columns under multi-condition impact loads - Liu, Yang; Liu, Guozhu; Li, Jingxi; Zhen, Yadong; Jiang, Wei (Frontiers in Earth Science, 2026)
This study focuses on the performance of hydraulic support columns under complex operating conditions. By constructing a finite element model that accounts for actual connection relationships and contact nonlinearities, mechanical simulation tests were conducted to thoroughly analyze their dynamic response. The results indicate that under impact loads, the stress response of the key components of the hydraulic support column exhibits a three-stage characteristic: “impact transient-dynamic adjustment-steady-state transmission.” The maximum stress at the secondary guide sleeve reaches 1735.7 MPa, significantly higher than other components, necessitating focused optimization. The middle cylinder bears the primary stress transmission task during axial load transfer, with a stress exceeding 200 MPa over a length of 600 mm–50% longer than the bottom cylinder—and the maximum stress in the middle cylinder is 1.4 times that of the bottom cylinder. Under radial load, a ring-shaped high-stress zone forms at the bottom of the cylinder wall in the bottom cylinder, with stress values reaching 589.31 MPa. The stress in the fixed-end weld zone is less than 150 MPa, showing a significant difference. These conclusions provide important theoretical basis for the structural optimization design and service life improvement of hydraulic support columns, demonstrating significant engineering application value.